Crossing systems in Epidendrum nocturnum Jacq. (Orchidaceae) - Silva Stort, Maria Neysa; Santos Pavanelli, Elza Aparecida dos (Revista de Biología Tropical, 1986)
Unter greenhouse condictions Epidendrum nocturnum (Orchidaceae) produced many fruits by self-pollination and cleistogamy. These processes must be optional for the group, since intra- and interspecific pollinations abo lead to the formation of fruit having seeds with embryos. The seeds produced by different crossing systems were either without embryos or had 1 to 4. Extra embryos appear more frequently in fruits formed without artificial pollination. On the average, the seeds obtained by artificial cross-pollination germinated more than those removed from naturally formed fruits.